The fifth season - Jemisin, N. K. (New York : Orbit, 2015)
Three terrible things happen in a single day. Essun, masquerading as an ordinary schoolteacher in a quiet small town, comes home to find that her husband has brutally murdered their son and kidnapped their daughter. Mighty Sanze, the empire whose innovations have been civilization's bedrock for a thousand years, collapses as its greatest city is destroyed by a madman's vengeance. And worst of all, across the heartland of the world's sole continent, a great red rift has been been torn which spews ash enough to darken the sky for years. Or centuries. But this is the Stillness, a land long familiar with struggle, and where orogenes -- those who wield the power of the earth as a weapon -- are feared far more than the long cold night.
Keywords: End of the world -- Fiction; Mothers and daughters -- Fiction; Fantasy fiction